United Republic of Tanzania : 2011 Article IV Consultation and Second Review Under the Policy Support Instrument; Staff Report; Debt Sustainability Analysis; Informational Annex; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for the United Republic of Tanzania. (IMF Staff Country Reports; Country Report ;, 2011)
Tanzania has weathered the adverse shocks of recent years relatively well. Revenue collection for 2010-11 has fallen short of targets, constraining public spending and contributing to the emergence of arrears. Monetary policy has become less accommodative. The near-term economic outlook is subject to a higher-than-average degree of uncertainty with a rising risk of donor aid shortfalls and higher international fuel prices. Over the medium term, growth could gradually rise to 7 1\2 percent--thanks to large investments in mining and continued growth in the non-mining economy.